قصيدة ت. س. إيليوت "الرباعيات الأربع": توظيف العناصر الميستية لمعالجة حالة الشكوكية الفردية في فترة الحرب العالمية الثانية - الخير, محمود; قازاريان, مهير (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
Mysticism is a religious tradition that has long existed in every religion, culture, and literary form, and indicates a direct experience of the Divine. It has been a rich theme for poets who have long used it to add intensity and depth to their poetry. Some poets have employed certain mystical elements to convey certain perspectives and answers concerning international and individual issues. This research aims at illustrating how T. S. Eliot employs the mystical elements of "paradox", "the Center" and "Via Negativa" in his poem Four Quartets to remind his readers of their divine essence and the way they should follow in order to get salvation, and relief from the individual state of uncertainty, on the spiritual and personal levels, that prevailed in the time of atrocities and chaos of World War II. الميستية تقليد ديني موجود منذ زمن بعيد في كل ديانة وحضارة وشكل أدبي, وتشير إلى الإدراك المباشر للمقدس. لقد شكلت الميستية موضوعاً غنياً للشعراء الذين قاموا بتوظيفها لإضافة عمق وقوة إلى أشعارهم وقام البعض منهم بتوظيف عناصر ميستية محددة لإيصال وجهات نظر معينة أو للإجابة عن بعض القضايا على الصعيدين العالمي والفردي. يهدف هذا البحث إلى إظهار كيف قام ت. س. إيليوت بتوظيف عناصر "التناقض" و"المركز" و"الطريق السلبي" في قصيدته "الرباعيات الأربع" ليذكر قراءه بجوهرهم المقدس والطريق الذي عليهم إتباعه للوصول إلى الخلاص والراحة من الحالة الشكوكية على الصعيدين الفردي والروحي التي سادت في زمن الفظائع والفوضى إبان الحرب العالمية الثانية.